Crystal structure of 5-ethyl-6-[(3-methylphenyl)sulfanyl]pyrimidine-2,4(1H,3H)-dione, C13H14N2O2S - Al-Wabli Reem I.; Ghabbour Hazem A.; Lahsasni Siham; Al-Abdullah Ebtehal S.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C13H14N2O2S, triclinic, P1̅ (no. 2), a = 4.8885(2) Å, b = 10.3414(5) Å, c = 12.6056(6) Å, α = 95.162(2)°, β = 97.487(1)°, γ = 101.494°, V = 614.73(5) Å3, Z = 2, Rgt(F) = 0.0507, wRref(F2) = 0.1149, T = 100 K.